Voices that ever reverberate—in memory of Dr. Prof. Lawrence Grouse - Zeng, Guangqiao; Journal of Thoracic Disease, on behalf of (Journal of Thoracic Disease, 2016)
I really hope that I had not written up this memorial article—never—just as we do not worry about missing the sight of sunlight when we wake up every morning, or we stretch out our hands for help and somebody would hold them. We are not concerned too much, as though we should enjoy endless plenty of friendship, love, and salvation in life. I was wrong…